Retrospective Evaluation of the Effectiveness of a Synthetic Glue and a Fibrin-Based Sealant for the Prevention of Seroma Following Axillary Dissection in Breast Cancer Patients - De Luca, Alessandro; Tripodi, Domenico; Frusone, Federico; Leonardi, Beatrice; Cerbelli, Bruna; Botticelli, Andrea; Vergine, Massimo; D'Andrea, Vito; Pironi, Daniele; Sorrenti, Salvatore; Amabile, Maria Ida (Frontiers in Oncology, 2020)
Introduction: Seroma formation represents one of the most frequent post-operative complications of axillary dissection in breast cancer (BC) patients. We aimed to retrospectively explore the effectiveness of the intraoperative use of a synthetic cyanoacrylate glue (specifically Glubran®2) versus the intraoperative use of a fibrin sealant (specifically Tisseel) in reducing seroma formation compared to the use of none sealant in BC patients undergone breast surgery and axillary dissection. Materials and Methods: We conducted a retrospective, monocentric observational study on BC patients undergone axillary dissection associated with breast surgery. The axillary dissection was completed with the application of a closed suction drain and was preceded by the application of either Glubran®2 glue or Tisseel sealant or none sealant. We analyzed: quantity of serum drained in the first 3 post-operative days, lenght of hospitalization, days of permanence of axillary drain, seroma development, presence of post-operative infection signs. Results: 41 BC patients were considered. Based on the devices used during the surgical treatment, the patients were divided into 3 groups: group A (17 patients), to whom suction axillary drain was applied; group B (7 patients), to whom Tisseel and axillary suction drain had been applied; group C (17 patients), to whom Glubran®2 and axillary suction drain had been applied. Between the 3 groups we did not find significant differences in terms of amount of serum drained in the first 3 post-operative days, lenght of hospitalization and incidence of seroma. Group C mantained the axillary drain a significantly lower number of days with respect the other 2 groups (p=0.02) as well as had a lower incidence of post-operative infections (6%) with respect to group A (23%) and group B (57%) (p=0.02). Conclusions: We did not find any evidence that the use of surgical glues may reduce the formation of seroma following axillary dissection in BC patients. Nevertheless, the use of cyanoacrylate glue in association with closed suction axillary drain seems to contribute to the reduction of days of axillary drain permanence and of post-operative infections, which are known factors delaying the schedule of any adjuvant oncological therapies.